The requiems of Brahms and Verdi - Pennels, Geraldine Murtel (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1994)
The aim of this thesis is to compare the Requiems of Brahms and Verdi, two composers who are both amongst the greatest in our Western musical history, but completely different in significant aspects, the one being by nature introspective, serious, and even inclined towards melancholy in his creative work, whether done in a religious context or not; and the other being first and foremost a composer of operas, thus specializing in music for the stage or theatre, presupposing extroversion and even a degree of flamboyancy. Brahms never wrote any operas but his oeuvre is enhanced by symphonies, sonatas and concertos of serious intent, and especially by a body of wonderful chamber music (which is perhaps the most intimate genre in Western instrumental music). Verdi, on the other hand, is known almost exclusively for his operas, and wrote little else. Then Brahms was one of the great composers of the German Lieder, again a markedly intimate genre, which suggests that he paid constant attention to fine detail. In contrast, Verdi's mentality was that of the Italian opera composer who is more concerned with flowing melodic beauty, which is a "translation into music" of the meanings and tendencies of the text.
Keywords: Brahms, Johannes, 1833-1897 -- Requiems; Verdi, Giuseppe, 1813-1901 -- Requiems; Requiems -- History and criticism; Requiems